Falls among the elderly - Weronika Topka; Małgorzata Maria Kwiatkowska; Natalia Skierkowska; Monika Prylińska; Wiktoria Gajos (Kazimierz Wielki University, 2020)
Falls are a significant problem among the elderly. Every third person falls at least once a year. Falls lead to injuries, limiting the mobility of the elderly. As a result of falls, serious fractures occur, which cause hospitalization and are the main cause of death due to accidents. The causes of falls are complex and most often arise from several overlapping factors. Efforts should be made to eliminate external factors in order to minimize the risk of falling among people over 60 years of age. Daily physical activity, individual assessment of risk factors and optimal adaptation of the environment play an important role in preventing falls. The aim of the study was to discuss the problem of falls in the population of geriatric patients.